2018
DOI: 10.18632/oncotarget.25389
|View full text |Cite
|
Sign up to set email alerts
|

The TGFα-EGFR-Akt signaling axis plays a role in enhancing proinflammatory chemokines in triple-negative breast cancer cells

Abstract: Triple-negative breast cancer (TNBC) is aggressive and typically has a poor prognosis. Chemokines have chemoattractant potential for cancer metastasis. Here, we investigated the chemokine signatures in BC subtypes and the underlying mechanisms that enhance proinflammatory chemokines in TNBC. Analysis from microarray dataset revealed that basal-like BC subtype including TNBC expressed dominantly proinflammatory chemokines, such as CXCL1 and 8, compared to non-TNBC. Chemokine PCR array confirmed the dominant che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 79 publications
3
12
0
Order By: Relevance
“…It is well known that AKT phosphorylation of BAD protein is a negative regulator of the proapoptotic function of BAD protein 56 . Consistent with our data, other groups have shown that activated AKT signalling is increased in TNBC 5760 and that inhibition of AKT signalling can increase the sensitivity of TNBC cells to nonspecific chemotherapies 61 . Others have shown that targeting the pro-survival BCL2 proteins of the BAD pathway, using the BH3 mimetic ABT-737, sensitized basal-like breast cancers to chemotherapy 62 .…”
Section: Discussionsupporting
confidence: 93%
“…It is well known that AKT phosphorylation of BAD protein is a negative regulator of the proapoptotic function of BAD protein 56 . Consistent with our data, other groups have shown that activated AKT signalling is increased in TNBC 5760 and that inhibition of AKT signalling can increase the sensitivity of TNBC cells to nonspecific chemotherapies 61 . Others have shown that targeting the pro-survival BCL2 proteins of the BAD pathway, using the BH3 mimetic ABT-737, sensitized basal-like breast cancers to chemotherapy 62 .…”
Section: Discussionsupporting
confidence: 93%
“…The significantly enriched categories included cell proliferation, immune response, cell differentiation, extracellular space, sequence-specific DNA binding, and transcriptional mis-regulation in cancer (Figure S4). The GO terms “cell proliferation” and “cell differentiation” were significantly enriched by several TNBC-associated genes, including CXCL1 , ELF5 , LIPG , and UCHL1 , which are known to play crucial roles in the initiation and metastasis of breast cancer and as potential TNBC diagnostic markers and therapeutic targets [31,32,33,34]. Genes involved in immune response were also common in DMEGs, implying that some immune-related DMEGs can be potential therapeutic targets for TNBC [35].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it might be possible that miR-23c acts as tumor suppressor in TNBC cell lines and that EGFR activation in MSCs contributes to breast cancer progression through the downregulation of such miRNA in the microenvironment. In addition, as MDA-MB-468 and MDA-MB-231 cells express EGF-related ligands [ 29 , 30 ], we can hypothesize that breast cancer cells, through the secretion of TGFα, educate MSCs to promote breast cancer progression by repressing miRNAs that act as tumor suppressors, such as miR-23c. The fact that the same miRNAs might act as tumor suppressors or as oncogenes might depend on the context.…”
Section: Discussionmentioning
confidence: 99%